Justification of parameters and development of layout solutions for the irrigation network of drip irrigation systems for gardens - Andrey S. Shtanko; Viktor N. Shkura (Мелиорация и гидротехника, 2025)
Purpose: to develop a methodology for designing an irrigation network of drip irrigation systems for commercial fruit gardens. Materials and methods. The empirical basis is the results of 9-year studies by the authors, carried out on 12 experimental sites in the gardens of Rostov region. The used methodological approach provides for generalization of a set of individual, previously established author's dependencies, calculation methods and layout and design solutions for the elements of drip irrigation network. Results and discussion. The developed methodology for designing an irrigation network provides for: 1) establishing the initial data for design; 2) determining the erosion-safe emitter flow rate and water supply rate per an emitter; 3) determining the parameters of irrigation lines and selecting a single-, double- or three-line irrigation module; 4) determining the parameters of the irrigation pipeline and developing a layout and design solution for the irrigation module. The acceptability of the methodology was tested under the conditions of the commercial garden in Neklinovsky district Rostov region. Based on the calculation results, a two-line design based on a 16 mm diameter irrigation pipe with through-type compensating emitters with a flow rate of 2.0 l/h and a spacing of 0.9 m is recommended as an irrigation module. The irrigation module includes an irrigation pipeline with a diameter of 68.8 mm and 60 irrigation lines (30 two-line irrigation modules). The introduction of a scientifically substantiated irrigation network led to an increase in yield by 28.8 % and an economic effect of 202.52 thousand rubles/ha. Conclusions. As a result of the conducted research and generalization of the obtained results, a methodology for designing an irrigation network of drip irrigation systems for commercial gardens was proposed, taking into account the garden soil and climatic conditions, phenological features of fruit crops, as well as features of the drip irrigation technology for perennial tree-fruit crops.